Production of cross-linked enzyme aggregates (CLEA) amylase from cocoa pod husk (CPH) for detergent application - Arab, Sonia Hadj (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
In Malaysia, large quantities of Cocoa Pod Husk (CPH), a by-product of cocoa industry are produced and generally go to waste, leading to problem in waste management. CPH was known to contain several enzymes and amylase is one of them. Knowing the potential of amylases has in several industries, this research aims to optimally extract amylase from CPH, and this was followed by immobilization via Cross-linked Enzyme aggregate (CLEA) technology for further stabilization. It is pertinent to maximize the extraction yield and to optimize the extraction process. For that matter, One-Factor-At-a-Time (OFAT) strategy was first carried out to determine the maximum values of the process parameters, and this was followed by adopting a Face Centered Central Composite Design (FCCCD) strategy under the Response Surface Methodology (RSM). The effect of independent parameters, namely, the concentration of buffer, the pH of buffer and the concentration of CPH (w/v %) of the extraction process on amylase activity was studied. Further on, the most active CLEA-amylase was prepared using the same statistical strategy, that is, OFAT followed by FCCCD on three independent parameters, and they are the concentration of three moieties, namely, acetone (as precipitant), glutaraldehyde (as cross-linker) and bovine serum albumin, (BSA) (as additive). The characterization of CLEA-amylase was compared with free amylase in terms of pH and temperature optimum, pH and temperature stabilities and kinetics parameters. Reusability of CLEA-amylase was also conducted. CLEA-amylase was analyzed by FESEM for morphology, FTIR for structural identity and finally applied to detergent for the capability in stain removal. The results show that the highest amylase activity (11.48 U/ml) was observed when the extraction was conducted with sodium phosphate buffer pH 7, 150 mM buffer with 7% (w/v) CPH. The highest activity in CLEA-amylase, with 92.24% recovery based on free enzyme activity, was when the preparation was done using 50% acetone, 60mM glutaraldehyde and 1.2 mg/ml BSA. The optimum temperature of amylase increases from 45 to 65oC and the optimum pH changes from 7 to 9 when immobilized. A systematic study of the stability of CLEA and free enzyme was taken with regards to temperature (25-100°C) and pH (5-12), and for both factors, CLEA-amylase showed higher stability than free amylase. Assuming that the enzymatic reactions follow the Michaelis-Menten kinetic, the KM of free amylase and CLEA-amylase are 0.675 and 1.0443 respectively, whereas the Vmax for free and CLEA-amylase are 3.44 and 2.71 respectively. The prepared CLEA-amylase was found to be able to be recycled six times, after which it still retained 30.87 % of its former activity. For applying in detergent, CLEA-amylase showed high stability against several detergent components and alkalinity agents and its addition in enzyme-free commercial detergent had improved the stain removal. In short, this study could be a stepping stone for the production of immobilized amylase in large scale so that it could be used in wider industrial applications. Future studies should incorporate different types of precipitating agents, as well as, the cross-linker to further optimize the CLEA preparation.